Introducing Undergraduates to Intensive Scholarly Work in the Humanities. - DeCosmo, Janice; McKinstry, Jill (International Journal of the Humanities, 2005)
Engaging undergraduates in research became a national focus for institutions of higher education in the mid-1990's. At a large research university, ‘research’ often means ‘science’. But, at the University of Washington, research and scholarship in the humanities are highlighted through initiatives such as the Simpson Center for the Humanities, the Summer Institute in the Arts and the Humanities, and the Library Research Award. The three-year-old Summer Institute, a collaboration of the Undergraduate Research Program and the Simpson Center for the Humanities, offers twenty students the opportunity to develop an original, individual project through the exploration of interdisciplinary source materials and advanced research methods with four faculty leaders. Students' projects are substantial and exemplary pieces of research, distinguished from routine course work and often of publication quality. Faculty from art, literature, music, history, international studies and other areas have led Institute students in their study of interdisciplinary themes exploring textual innovations, globalization, and trauma and memory. The Library Research Award recognizes students who produce significant research projects requiring use of the library, its resources, and collections. Offering a Library Research Award supports the mission of the library to enrich the quality of life and advance intellectual discovery by connecting people with knowledge, for it recognizes the coordinated effort of the faculty, the student and the library in research and publication. For the humanities, fine arts, and discursive social sciences, this program provides a public forum for discourse and discovery.